Teori Perang vs Teori Perang yang Adil: Sebuah Studi Perbandingan (pp. 139-154) - Syasya Yuania Fadila Mas'udi (JURNAL KEAMANAN NASIONAL, 2023)
This study aims to see whether just war does exist, or whether the existence of the theory is only to satisfy moral principles by those who are concerned with the ethics of war. As we know that war is destructive for whatever the reason. Although states do not wage war anymore, it does not mean that the world is safe from war. Therefore, just war theory is intended to make war justifiable, that there are justifiable reasons for a state to declare war. In answering the research question whether just war exists, the researcher compared the just war theory with the theory of war. The research method that used is qualitative, comparative study, while the type of research used in this research is descriptive research and data collection techniques are carried out using literature study method. The results showed that basically the theory of war and the just war theory are basically contradictory to each other so that in practice war will never be just. Keywords: ethics of war, just war theory, theory of war